Analisis sistem bagi hasil muzara’ah dan Mukhabarah pada usahatani padi dan implikasinya terhadap kesejahteraan keluarga petani penggarap dan pemilik lahan di Kecamatan Praya Timur - Abdul Mutallib (Lembaga Penelitian dan Pendidikan Mandala, 2015)
The purpose of this study is to investigate the implementation of the profit sharing system muzara’ah and mukhabarah on rice farming activity in terms of Islami persefektive and its implication toward the walfare of families of the sharecroppers and landowners in the district of East Praya Central Lombok. This is qualitative research whos primary data were obtained by direct observation and interviews while the secondary data were obtained from the sub-district office in East Praya and institution assosiated with agriculture and other source.Analysis of the qualitative data was conduted inductively; a specific case or symptomis analysed and, later on, a more general conclusion are withdrawn.The results summarizes the implementation of the profit sharing system of muzara’ah and mukhabarah on rice farming activity in East Praya district as follows: conceptually, the prsctice of nyakap in East Praya basically the same with the concept of Muzara’ah and Mukhabarah in Islam. The contract is simply oral. There are two kind of costs, namely, the overall cost of landowners (Muzara’ah) and the cost borne by thesharecroppers (Mukhabarah). Profit sharing is carried out by reducing the cost inadvance. The allocation of these sharing for sharecroppers family is still for daily consumptiononly while for landowners, the allocation is more for future saving. In terms of walfare measurement, sharecroppers can only fulfill their basic needs while the owner of the land can do more to satisfy their living needs